Density in mandibular trabeculae of beta thalassemia major patients at the age of 11-13 years - Biyantini, Nisa Milati; Oscandar, Fahmi; Riyanti, Eriska (Padjadjaran Journal of Dentistry, 2012)
Introduction: Density of mandible trabeculae is defined as density of trabeculae at posterior region of mandibulae. Systemic diseases which can affect bone density are osteoporosis and many types of anemia, including which has significant influence that is beta thalassemia major. The objective of this investigation was to obtain the data of density in mandible trabeculae of beta thalassemia major patients at the age of 11-13 years. Methods: The descriptive method was used in this study and the samples were selected using the total sampling technique. 15 periapical photos were obtained using the total sampling echnique. The periapical photos are administered using 3D-Doctor software. Data were analyzed using simple mean value formula. Results: Statistical count resulted in the minimum score of sample which was 98, 039 grayscale, the maximum score of sample which was 231, 34 grayscale, and the range score of sample which was 126.503 grayscale Conclusion: Density of mandible trabeculae of thalassemia beta major patients at the age of 11-13 is 126.503 grayscale.